ANLN, Regulated by SP2, Promotes Colorectal Carcinoma Cell Proliferation via PI3K/AKT and MAPK Signaling Pathway. Issue 2 (1st February 2022) - Liu, Yanwei; Cao, Pengwei; Cao, Feng; Wang, Song; He, Yan; Xu, Yanyan; Wang, Yong
Abstract: Background: Aberrant expression of Anillin (ANLN) has been shown to function in the development of multiple cancers. However, its effects on colorectal carcinoma (CRC) remain unclear. We aimed to explore the role of ANLN in CRC development. Methods: By real-time quantitative polymerase chain reaction (RT-qPCR), Western blot, and immunohistochemistry (IHC), we assessed the expression level of ANLN in CRC tissues and cell lines. The role of ANLN in CRC cell proliferation was evaluated by CCK-8 assays, colony formation assays, EdU assays and cell cycle assays. A mouse tumorigenic model was established to evaluate the in vivo function of ANLN. Results: We found that ANLN was overexpressed in CRC tissues and cell lines. Highly expressed ANLN correlated with tumor size, tumor number, and stage in patients with CRC. Silencing ANLN in CRC cell lines suppressed proliferation both in vitro and in vivo and induced G0/G1 cell cycle arrest. Downregulation of ANLN led to reduced phosphorylated levels of AKT and ERK. However, total AKT protein showed no change. SP2, a critical transcription factor, was implicated in the upregulation of ANLN. Conclusions: Our study demonstrated that ANLN regulates CRC cell proliferation via the PI3K/AKT and MAPK pathways, indicating that ANLN may represent a novel and effective target for CRC treatment.